N,S‐Codoped hollow carbon dodecahedron/sulfides composites enabling high‐performance lithium‐ion intercalation - Lu Chen (Wiley-VCH, 2021)
Abstract Lithium‐ion batteries are the predominant energy storage devices for portable electronic devices and hold great promise for renewable energies and sustainability. High capacity and long‐life anode materials are highly desired for the next‐generation Li‐ion battery with high energy density. Herein, a high‐performance anode electrode constructed with cobalt and zinc sulfides nanocrystals embedded within a nitrogen and sulfur co‐doped porous carbon is successfully designed bimetal‐organic frameworks as the precursor. Benefiting from synergistic effects of bimetal sulfides, the unique rhombohedral dodecahedral nanostructure with rough surface area and N,S‐codoped carbon matrix, such an anode material presents superior initial reversible capacity of 938.2 mA h g−1 with a high‐capacity retention of 65.6% after 100 cycles at 150 mA/g. The effective nanostructure design is expected to open a venue to construct high‐performance materials for energy and environment applications.